Sistem Bonus Bisnis Multi Level Marketing Pada PT. Melia Sehat Sejahtera di Kabupaten Jember Perspektif Akad Ju’alah - Mohammad Firmansyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
One of the businesses that is growing rapidly in Indonesia today is the multi-level marketing (MLM) business. MLM is a method of marketing goods or services from a system of selling goods directly through a marketing program in the form of more than one level, where business partners get sales commissions and sales bonuses from the sale of goods or services carried out by themselves and network members in their group. In general, this thesis discusses the multi-level marketing (MLM) business at PT.Melia Sehat Sejahtera in Jember district, with problems namely (1) how is the bonus system at PT.Melia Sehat Sejahtera in Jember district, (2) how is the review of Sharia Economic Law against the bonus system at PT. Melia Sehat Sejahtera in Jember district. This study uses a field research method with a descriptive approach which is useful for providing information, facts and data regarding the network bonus system at PT.Melia Sehat Sejahtera in Jember district. Then the data was analyzed using qualitative methods to uncover events, phenomena, facts and circumstances that actually occurred in the field. From this study it can be concluded that the bonus system at PT. Melia Sehat Sejahtera in Jember district has five types of bonuses, namely: sponsor bonuses, leadership bonuses, retail bonuses, retail group bonuses and unilevel bonuses. Meanwhile, according to Sharia Economic Law, the bonus system at PT. Melia Sehat Sejahtera in Jember district isThis can be done because it is in accordance with Islamic law.